Performing science-fiction fandom through debating controversy: Communicative leisure, collective memory and Rogue One: A Star Wars Story, below the line at The Guardian. (1st March 2020) - Spracklen, Karl
Star Wars has become one of a handful of science-fiction franchises that have defined and shaped what Adorno calls the modern culture industry. The original trilogy challenged the way Hollywood financed and marketed its movies and made George Lucas incredibly rich. Star Wars fans bought tickets for re-releases, special editions and the notoriously egregious prequels, as well as a seemingly endless range of merchandise. When Lucas sold the franchise to Disney new movies were promised, including what became the stand-alone prequel Rogue One: A Star Wars Story. In this article, I am interested in exploring how people react in publicly accessible online spaces, as these are key spaces for the performativity of digital communicative leisure. Specifically, I am interested in how fans of the original trilogy and the Star Wars franchise critiqued or defended the film and Star Wars more broadly through a detailed analysis online comments below the line reacting to review by film critic Mark Kermode published in a middle-class, liberal newspaper: the UK-based The Guardian. This review and its comments below the line represent a snapshot of what middle-class liberals might feel able to write about the film and their own Star Wars fandom. This analysis will also be extended to critiques made by people seeking to distance themselves from Star Wars and all that Star Wars fandom may entail, as a performativity of anti-fandom. I will show that for fans collective memory is used to try to construct authenticity and ownership of Star Wars, but that collective memory is only ever temporarily negotiated.